Peran dan Ketangguhan Orang Tua Dalam Membangun Akhlak Siswa pada Masa Pandemic Covid-19 di MTs Insan Sejati - Fika Fikriyah; Bahagia Bahagia (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
Morals are very important for every Muslim, and morality itself must be instilled in a child even from an early age as the next generation. The outbreak of the COVID-19 pandemic has greatly impacted children's morals so that the role of parents and their resilience is really tested so that children continue to receive moral education, considering the role of teachers in moral education is reduced during online learning. The method used in this study is a qualitative method with a descriptive analysis approach. This study aims to find out how tough parents are and the role of parents in educating children's morals during the covid-19 pandemic. The method used for sampling in this research is purposive sampling. Data was collected by observation, in-depth interviews, and documentation. The researcher met 1 respondent from the principal and 3 respondents from parents. Researchers conducted this research at Madrasah Tsanawiyah Insan Sejati, which was carried out for one month. In the results of this study, the researchers found that the role of parents was quite maximal in efforts to build children's morals, and also the resilience of parents who were carried out to deal with the covid-19 outbreak so that their children could still take a good and proper education. Keywords: Morals; the role of parents; Parental toughness